PRIORITAS PENANGANAN BANJIR KECAMATAN TELANAIPURA KOTA JAMBI TAHUN 2012 - Aditya Arif, Dian (Pendidikan Geografi, 2013)
AbstractThe objectives of research are: (1) to find out the distribution of vulnerable-to-flood area in Telanaipura Subdistrict of Jambi City in 2012, (2) to find out the distribution of flood hazard area in Telanaipura Subdistrict of Jambi City in 2012, and (3) to find out the priority of Flood management in Telanaipura Subdistrict of Jambi City in 2012.This research used a descriptive qualitative method with terrain unit as the unit analysis. The area of study included entire area of Telanaipura Subdistrict consisted of 11 kelurahans. The data obtained included primary and secondary data. Techniques of collecting data used were documentation, observation, and interview. Techniques of analyzing data used to find out the distribution of vulnerable-to-flood area were scoring and overlay with the following parameters: landuse map, drainage channel density map, and slope declivity map. Before overlay process, each parameter weighing faktor was determined first according to the effect of flood vulnerability. The distribution of flood hazard area was analyzed using scoring and overlay technique with the following parameters: flood vulnerability map and intensively land use map. The flood management area was analyzed using scoring and overlay techniques with the following parameters: flood danger map and dasimetric population density map.Kata kunci : Rawan banjir, bahaya banjir, prioritas penanganan banjir